Effect of cadmium on the performance of partial nitrification using sequencing batch reactor. (May 2019) - Zhang, Liqiu; Fan, Jingjing; Nguyen, Hang N.; Li, Shugeng; Rodrigues, Debora F.
Abstract: Partial nitrification (PN) in sequencing batch reactors (SBR) was investigated in the presence of cadmium to simulate treatment of landfill leachate containing heavy metals. Different pH conditions were investigated in the SBR to determine the optimum pH to establish PN, which was 7.5. After successful establishment of the PN process, different concentrations of cadmium (Cd) were added into the SBR to evaluate the heavy metal influence on the PN process. The results showed that PN activities were not affected by low concentrations of Cd (< 5 mg L −1 ). However, the PN efficiency decreased by more than 30% when Cd influent reached 10 mg L −1 . This was mainly due to the toxicity of Cd under high concentrations, which decreased the activity of microorganisms, leading to failure of the PN process. The effects of different Cd concentrations were further investigated toward ammonia oxidizing bacteria (AOB), nitrite-oxidizing bacteria (NOB), and heavy metal resistant bacteria (MerA) via quantitative real-time PCR. The overall change in the SBR microbial population was also determined via 16S rRNA metagenomics. The results indicated the AOB and NOB were able to tolerate and function well under concentrations below 5 mg L −1 of Cd. In the Cd augmented reactors, Bacteroidetes and Proteobacteria were the most dominant phyla. At the genus level, Chryseobaterium and Flavobacterium, were the most abundant and tolerated Cd at 5 mg L −1, while some microbial groups, such as Dechloromonas and Citrobacter resisted to 10 mg L −1 Cd but did not contribute to PN. Graphical abstract: Image 1 Highlights: pH 7.5 was optimum for partial nitrification on simulated landfill leachate. Partial nitrification occurred effectively with 5 mg L −1 cadmium. Partial nitrification failed with 10 mg L −1 Cd. Small groups of microbes resisted to Cd and could remove ammonia effectively.